PENGEMBANGAN E-MODUL BERBASIS POWTOON PADA MATA PELAJARAN MATEMATIKA MATERI BANGUN RUANG KUBUS DAN BALOK - Afifah Yuwanita Nurlina; Fitri Siti Sundari; Tatang Muhajang (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to develop a Powtoon-based e-module for mathematics instruction, specifically focusing on the topics of cube and rectangular prism in the fifth-grade class of SDN Gunung Dahu, Bogor Regency. The study employs a Research and Development (R&D) approach using the ADDIE research model (Analysis, Design, Development, Implementation, Evaluation), which encompasses phases of analysis, planning, development, testing, and evaluation. Data collection involved interviews with fifth-grade homeroom teachers, observations of students, and an analysis of student responses to the developed e-module. The evaluation results from experts in media, language, and content revealed an average final percentage of 95.23%, while students responded positively with an 89.86% approval rate. This research makes a significant contribution to the development of effective and engaging mathematics learning resources, demonstrating the potential of Powtoon-based e-modules as an efficient tool for enhancing students' understanding and interest in the topics of cubes and rectangular prisms.